1969
DOI: 10.1073/pnas.63.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Repression of the Histidine Operon, Ii. The Role of the First Enzyme in Control of the Histidine System

Abstract: Abstract.-Recent studies on repression of the enzymes for histidine biosynthesis in Salmonella typhimurium demonstrated that the kinetic pattern in which the enzymes become repressed is influenced by the state of the feedbacksensitive site of the first enzyme of the pathway (Kovach et al., J. Bacteriol., 97, 1283). In the present study we demonstrate that under certain conditions alteration of the feedback-sensitive site of the first enzyme prevents repression of the histidine operon. We conclude that the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
35
0

Year Published

1970
1970
1979
1979

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 21 publications
8
35
0
Order By: Relevance
“…Such a possibility is not without precedence. For example in Salmonella typhimurium, charged histidyl t-RNA both inhibits and represses the formation of ATP phosphoribosyl transferase, the enzyme at the branch point in the pathway leading to histidine (10). The apparent discrepancy between the concentration dependence of the effect of itaconate in vivo and in vitro could be the result of transport or of metabolic modification to less inhibitory forms.…”
Section: Discussionmentioning
confidence: 99%
“…Such a possibility is not without precedence. For example in Salmonella typhimurium, charged histidyl t-RNA both inhibits and represses the formation of ATP phosphoribosyl transferase, the enzyme at the branch point in the pathway leading to histidine (10). The apparent discrepancy between the concentration dependence of the effect of itaconate in vivo and in vitro could be the result of transport or of metabolic modification to less inhibitory forms.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of repression of biosynthetic enzymes, the situation is not as well understood, although there has been evidence that control might be exerted at the level of both transcription and translation (22), with strong evidence for translational control (23). There is additional evidence that repression might involve tRNAs (24,25), aminoacyl-tRNA synthetases (26)(27)(28), and completed biosynthetic enzymes (1)(2)(3)(4)(5)(6)(7). The best evidence that a completed enzyme might be involved in the repression of other enzymes of the same pathway has been obtained in the histidine pathway of S. typhimurium, where it has been shown that the binding site for feedback inhibition of the first enzyme of the histidine pathway is also involved in repression (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, the model, in its original form, has proven inadequate for the explanation of many of the facts surrounding repression and derepression of enzymes involved in biosynthetic pathways (3). Several authors have proposed alternative models of regulation for these systems (4)(5)(6)(7)(8)(9)(10). One such alternative is the autoregulatory model proposed by Hatfield and Burns (11) in 1970, which was formulated to explain the repression pattern observed for enzymes involved in biosynthesis of the branched-chain amino acids, visoleucine, r-valine, and L-leucine (Fig.…”
mentioning
confidence: 99%